Mapeo científico en la búsqueda de información. Caso de estudio: enfermedades infecciosas en bovinos - Ballesteros-Ricaurte, Javier-Antonio; Avendaño-Fernández, Eduardo; González-Amarillo, Angela-María; Granados-Comba, Adriana (Revista Científica, 2021)
The steps to be followed in a scientific mapping process on a research topic are proposed using tools that allow identifying different relationships and performing analyses between articles, taking the topic of infectious bovine diseases as a case study. The employed methodology is based on six steps that go from information retrieval through systematic literature review to the visualization of the results by means of the SciMAT scientific map analysis tool, mainly using the keywords, the H index, and the occurrence of the terms in the text. As a result, it is found that studies on infectious bovine diseases have focused on subtopics such as disease outbreaks, the treatments used, prevention models, and analysis of laboratory samples. On the other hand, it is indicated that further studies are needed on the use of computer tools or the development of applications that use modern techniques such as artificial intelligence and machine learning to support the analysis, control, and eradication of infectious bovine diseases.